The Impact of Islamic Religious Education on the Development of Early Childhood Religious and Moral Values During the COVID-19 Pandemic in Indonesia and Malaysia - Munastiwi, Erni; Rahmatullah, Bahbibi; Marpuah (Jurnal Pendidikan Islam, 2021)
When the world is busy with the COVID-19 virus outbreak, various sectors experienced a significant impact, especially in the education sector, which requires children to carry out learning activities from home. This study aims to determine the effect of Islamic religious education on early childhood's religious and moral values during the COVID-19 pandemic. This study uses a quantitative analysis method of product-moment correlation through a t-test to test the significance of the effect of the independent variable on the dependent variable. The study results found that the hypothesis using the t-test showed that the independent variable of Islamic religious education was proven to significantly influence the dependent variable on the development of religious and moral values of early childhood. Then through the t-test, it can be seen that the significance value of 0.534 is greater than the 0.05 significance level. Thus, Ha is accepted, religious education has a significant effect on the development of religious and moral values of early childhood during the COVID-19 pandemic. This study contributes to a deep understanding that Islamic religious education affects the development of religious and moral values of early childhood even in the Covid-19 pandemic situation. The role of parents is a good role model for children to apply religious and moral values through Islamic religious education.